Shell Structures and Functionalist Forms of Hospital Architecture (How Both Factors Influence on the Emotions of the Patient and the User) - Sami, Sania (New Approaches in Engineering Research Vol. 1, 2021)
As one of requirements of human life is health and hygiene, so, some places should be forecasted for these affairs to being true. Hygiene and health will be divided to physical and mental branches which researchers states that if mental health is provided, physical health can be easily available and finally, human can easily take his course during treatment which obtain healthy life. It finally causes creating great works and massive movements in human life. One characteristics of a good medicinal center is easy and rapid access, so that patients can have access to these centers with minimum time. This access is defined from the place where the patient resides to the interior spaces of medical centers, and many factors affect the quality of this path. On factor is the human view of form, how to create a different form by designing an external shell and embedding the original structure under this shell so that it can be developed and expanded at the same time, and at the same time be inviting, so that clients and users move towards these centers and walk indoors comfortably and away from double stress. Doing studies and data collection and information evaluation is of the basics of designing and requires a full research design. The present study is to provide a comprehensive cognitive understanding of all those involved in architectural design for hospital building and patients. Besides, studying and collecting all available written and verbal references, principles and optimized guidelines of designing an efficient hospital were extracted in order to meet medicinal and psychological needs of patients.